A prospective cohort study of hypoalbuminemia as risk factor of wound healing in diabetic foot: a study from tertiary hospital in south India - Edakkepuram, Unnikrishnan; P. C., Sheeja; Gopi, Ellikunnel Vithon (International Surgery Journal, 2017)
Background: Diabetic foot ulcers is a major complication of diabetes mellitus, and precedes >80% of all diabetes related lower leg amputations. One of the risk factors in non-healing diabetic ulcer is low serum albumin level. The objectives of this study were to study the effect of low serum albumin level in patients with diabetic foot ulcer and to study the factors affecting wound healing in diabetic ulcer. Methods: Prospective cohort study in a tertiary hospital. Results: The mean age among study was 57.8 out of which 68.3% were males and 31.7% were females. 55% patients presented with slough over ulcer, 29.2% patients presented with healthy granulation and 15.8% patients presented with extensive wound infection. Among study group 50% patients had good glycaemic control and 50% patients had poor glycaemic control. Conclusions: Low serum albumin level is one of the attributable risk factor of non-healing ulcers in diabetic foot. Poor glycaemic status is also a risk factor for non-healing ulcer.